Natrah, 1937-2009 Nadra @ Huberdina Maria Hertogh @ Bertha : cinta, rusuhan, air mata - Fatini Yaacob (Penerbit Universiti Teknologi Malaysia, 2010)
Biography of Maria Hertogh, a Dutch girl adopted by a Malay family and the central focus of racial riots on 11 December 1950 in Singapore.